Solicitation matters: Cultural differences in solicited and unsolicited support provision - Hashimoto, Hirofumi; Ohashi, Takuma; Yamaguchi, Susumu (Frontiers in Psychology, 2022)
Two studies aimed to examine cultural differences in social support provision, with or without solicitation, in Japan and the United States (US). In Study 1, we conducted a replication study of Chen et al. (2012) with Japanese university students. We found that the Japanese participants did not provide social support when it was not solicited, as compared with when it was solicited. Furthermore, in Study 2, participants were asked to respond to a questionnaire regarding a hypothetical stressful situation experienced by a close other and to indicate their willingness to provide support. We confirmed our hypothesis that Japanese participants hesitate to provide unsolicited support to close others (such as family members or close friends), even when they recognize that the close others are in need, whereas the American participants do not hesitate to provide such support. Contrastingly, regarding solicited support, the Japanese and Americans were equally ready to provide support, as hypothesized. The cultural difference in social support resides in the provision of unsolicited support. These results suggest that differences in culturally appropriate responses to needy people are responsible for the difference in the provision of unsolicited vs. solicited social support.